Antithrombotic therapy in patients with non-valvular atrial fibrillation undergoing percutaneous coronary intervention: should we change our practice after the PIONEER AF-PCI and RE-DUAL PCI trials? - Dürschmied, Daniel; Katus, Hugo (Clinical research in cardiology, 2018)
The number of patients with atrial fibrillation undergoing percutaneous coronary intervention (PCI) is increasing. Since these patients have a CHA2DS2-VASc score of 1 or higher, they should be treated with oral anticoagulation to prevent stroke. However, combination therapy with oral anticoagulation for prevention of embolic stroke and dual platelet inhibition for prevention of coronary thrombosis significantly increases bleeding complications. The optimal combination, intensity and duration of antithrombotic combination therapy is still not known. In the rather small randomized WOEST trial, the combination of a vitamin K antagonist (VKA) and clopidogrel decreased bleeding compared to the conventional triple therapy with VKA, clopidogrel and aspirin. In the PIONEER AF-PCI trial, two rivaroxaban-based treatment regimens significantly reduced bleeding complications compared to conventional triple therapy without increasing embolic or ischemic complications following PCI. Dual therapy with rivaroxaban and clopidogrel appeared to provide an optimal risk-benefit ratio. In the RE-DUAL PCI trial, dual therapy with dabigatran also reduced bleeding complications compared to conventional triple therapy. With respect to the composite efficacy end point of thromboembolic events (myocardial infarction, stroke, or systemic embolism), death, or unplanned revascularization dabigatran-based dual therapy was non-inferior to VKA-based triple therapy. The upcoming trials AUGUSTUS with apixaban and ENTRUST-PCI with edoxaban will further examine the use of NOACs in this setting. While recent guidelines recommend NOAC-based dual therapy in only a subset of patients (those who are at increased risk of bleeding), the available data now suggest that this should be the preferred choice for the majority of patients. Adding aspirin to this primary choice for up to 4 weeks in patients at especially high ischemic risk would likely prevent atherothrombotic events, but this needs further investigation. Taken together, it is time to adjust our practice and move to dual therapy consisting of a NOAC plus clopidogrel in most patients.
Gesehen am 25.06.2019